Emerging role of human endogenous retroviruses in mothers with history of perinatal depression and risk of neurodevelopmental disorders in offspring: Results from a pilot study - Chiara Cipriani; Martina Siracusano; Martina Giudice; Vita Petrone; Assia Riccioni; Elisa Carloni; Ilaria Adulti; Irene Sferra; Martino Tony Miele; Marialaura Ferrara; Enrico Garaci; Claudia Matteucci; et al. (PLoS ONE, 2026)
Perinatal depression (PD) actually affects 10−15% of pregnant women and represents one of the most debated topics as potentially implicated in offspring neurodevelopmental disorders etiology, particularly Autism Spectrum Disorder (ASD). Scientific evidence supports the role of Human Endogenous Retroviruses (HERVs) in ASD, as a link among environmental stimuli, epigenetic remodeling and biological processes. The aim of the present study was to characterize the expression profile of different HERVs and selected cytokines in peripheral blood mononuclear cells from women who have experienced PD in comparison to women without history of PD and their respective children stratified according to ASD diagnosis, by RT Real-Time PCR. We showed that ASD children and their PD mothers share abnormal expression of pHERV-W, syncytin-2 and IL-6 likely influenced by the common environment, maternal status, genetic predisposition, or postnatal factors. Of note, mothers with a history of PD were also evaluated at the time of blood sampling using the Hamilton Depression Rating Scale, and a positive correlation with pHERV-W levels was observed. Together with previous results in preclinical models and human studies, our results support the role of HERVs in autism as a contributing factor in creating an adverse environment for normal neurodevelopment, strengthening the view of a mother-child association in the context of autism. PD being associated with the altered activity of HERVs could be considered to be an additional risk factor in the pathogenesis of autism.